Willingness to accept local wind energy development: Does the compensation mechanism matter? - García, Jorge H.; Cherry, Todd L.; Kallbekken, Steffen; Torvanger, Asbjørn (Energy policy, 2016)
Wind power development projects often include compensation for the affected communities, but little is known about the efficacy of the alternative compensation mechanisms. This study addresses this question by examining the relative potential of private and public compensation. We conduct a Choice Experiment (CE) that investigates household preferences of compensation for the local siting of a hypothetical wind park. Households chose among different alternatives, where each alternative was characterized by three varying attributes: the number of turbines, the level of private compensation, and the level of public compensation. Results indicate the wind park imposes welfare losses to local residents and non-local recreational users, with about 35% of these losses corresponding to non-use values. Findings show that households prefer public compensation to private compensation, with household’s willingness to accept being lower with public compensation than private compensation. This finding suggests that estimates of local resistance to wind development depends on the compensation mechanism. •Local resistance to wind development depends on the compensation mechanism.•Households prefer public compensation to private compensation.•This result may be explained by under-provision of local public goods.